The Cryptococcus neoformans capsule: lessons from the use of optical tweezers and other biophysical tools - Pontes, Bruno; Frases, Susana (Frontiers in Microbiology, 2015)
The fungal pathogen Cryptococcus neoformans causes life-threatening infections in immunocompromised individuals, representing one of the leading causes of morbidity and mortality in AIDS patients. The main virulence factor of C. neoformans is the polysaccharide capsule; however, many fundamental aspects of capsule structure and function remain poorly understood. Recently, important capsule properties were uncovered using optical tweezers and other biophysical techniques, including dynamic and static light scattering, zeta potential and viscosity analyses. This review provides an overview of the latest findings in this emerging field, explaining the impact of these findings on our understanding of C. neoformans biology and resistance to host immune defenses.